Reator anaeróbio compartimentado para o tratamento de águas residuárias de suinocultura - Oliveira, Roberto Alves de [UNESP]; Duda, Rose Maria [UNESP]; Rodrigues Fernandes, Gracie Ferraz [UNESP] (Assoc Brasileira Engenharia Sanitaria Ambiental, 2014)
Water and soil pollution caused by the waste from the swine production causes severe environmental impacts in producing areas. An efficient alternative to reduce these impacts can be the use of high-rate anaerobic reactors. In this work, it was evaluated the effect of the swine wastewater with total suspended solids concentrations around 6.000 mg.L-1 in the anaerobic baffled reactor with three compartments. The volume of the first compartment was 210 L and of the second and third ones of 160 L. The anaerobic baffled reactor was submitted at hydraulic detention times of 56, 28 and 18 hours and to organic load rates of 5.0 to 10.1 g total COD (L.d)(-1). The highest total COD removals, of 42 to 68%, and volumetric methane productions, of 0.261 to 0.454 L CH4 (L reactor d)(-1), occurred in the second compartment.

A poluição da água e do solo causada pela suinocultura provoca impactos ambientais severos nas regiões produtoras. Uma alternativa eficiente para atenuar esse problema pode ser a utilização de reatores anaeróbios de alta taxa. Neste trabalho, avaliou-se o efeito das águas residuárias de suinocultura com concentrações de sólidos suspensos totais em torno de 6.000 mg.L−1 no desempenho do reator anaeróbio compartimentado, com três câmaras. O volume da primeira câmara foi de 210 L e da segunda e terceira de 160 L. O reator anaeróbio compartimentado foi submetido a tempos de detenção hidráulica de 56, 28 e 18 horas e a cargas orgânicas volumétricas de 5,0 a 10,1 g DQOtotal (L.d)−1. As maiores remoções de demanda química de oxigênio total, de 42 a 68%, e das produções volumétricas de metano, de 0,261 a 0,454 L CH4 (L reator d)−1, ocorreram na segunda câmara.
Anaerobic baffled reactor for treatment of swine wastewater
Keywords: Organic loading rate; Anaerobic sludge; Methane; Anaerobic reactor; Swine waste; Carga orgânica volumétrica; Lodo anaeróbio; Metano; Reator anaeróbio; Resíduos de suínos